MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN SEJARAH (KOMPETENSI DASAR PROKLAMASI KEMERDEKAAN DAN TERBENTUKNYA PEMERINTAHAN INDONESIA) MELALUI METODE BIMBINGAN INDIVIDUAL DI KELAS X I AKUNTANSI 2 SMK NEGERI 1 TASIKMALAYA - Mulyani, Leni Sri Dewi (Jurnal Inovasi dan Teknologi Pendidikan, 2024)
The problem in this research is whether students' learning motivation in History subjects can be increased through individual guidance methods in Class XI Accounting 2 SMK Negeri 1 Tasikmalaya. The aim of the research is to increase students' learning motivation in the History subject through individual guidance methods in Class XI Accounting 2 of SMK Negeri 1 Tasikmalaya. Meanwhile, the data analysis techniques used are quantitative and descriptive qualitative. This research uses Classroom Action Research, where the research action is stopped if the learning completeness criteria of 80% of the total number of research subjects have been achieved with an average score of more than 65. The subjects in this research were 36 students of Class XI Accounting 2 of SMK Negeri 1 Tasikmalaya in Lessons 2022/2023. Student learning motivation is measured based on individual learning completeness criteria. The results of the research showed that students' learning motivation in the attention aspect, students who had good grades was 62.5%, in cycle II increased to 93.75%, in the aspect of connection, students who had good grades was 62.5%, in cycle II increased to 81 .25%. In the self-confidence aspect, students who had good grades were 68.75%, in the second cycle it increased to 87.5%, and in the satisfaction aspect, students who had good grades were 62.5%, in the second cycle it increased to 93.75%, Conclusion from the results of research on increasing student learning motivation in History subjects through individual guidance methods in Class XI Accounting 2 of SMK Negeri 1 Tasikmalaya, it was declared successful